Giant major aphtha - Andrea E. Beretta; Eleonora Leoni; Dario A. Marletta; Stefano Veraldi (Dermatology Reports, 2024)
Major aphthae are usually located on the dorsum of the tongue, the mucosal surface of the lips and the palate. They are large, round or oval ulcers, with a whitish-grey bed, well-defined borders and erythematous halo. They are very often accompanied by severe pain. Major aphthae can take up to four months to heal, often with a scar. Relapses are possible. We present a case of “giant” major aphtha that was previously diagnosed as squamous cell carcinoma.